Maternal-Fetal Pharmacology of Cefatrizine in the First 20 Weeks of Pregnancy - Bernard, Betty (1977)
To evaluate maternal-fetal pharmacology of cefatrizine (BL-S 640), a new oral cephalosporin, a single oral 1,000-mg dose was administered to 33 gravidas (8 to 20 weeks' gestation) at varying intervals within 46 h of an elective therapeutic abortion by hysterectomy or intra-amniotic prostaglandin F(2a) induction. Mean maternal serum concentrations at 1, 2, 4, and 8 h were 3.7, 7.9, 6.5, and 1.6 μg/ml; beyond a 3-h peak, a half-life of 2.4 h was determined. Cefatrizine placental half-life was 4.4 h. None of the 11 fetuses from a prostaglandin F(2a) abortion revealed cefatrizine activity; in contrast, 17 of 22 fetuses from a surgical abortion demonstrated cefatrizine concentrations in two or more samples. Fetal cefatrizine levels were less than 3 μg/g or μg/ml in kidney and urine, less than 2 μg/ml in serum and bile, and less than 2.5 μg/g in lung. After a single maternal dose, cefatrizine has a wide distribution in the fetus in the first half of gestation.